Blood flow patterns during incremental and steady-state aerobic exercise - Coovert, D.; Evans, L. D.; Jarrett, S.; Lima, C.; Lima, N.; Gurovich, A. N. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Endothelial shear stress (ESS) is a physiological stimulus for vascular homeostasis, highly dependent on blood flow patterns. Exercise-induced ESS might be beneficial on vascular health. However, it is unclear what type of ESS aerobic exercise (AX) produces. The aims of this study are to characterize exercise-induced blood flow patterns during incremental and steady-state AX. We expect blood flow pattern during exercise will be intensity-dependent and bidirectional. METHODS: Six college-aged students (2 males and 4 females) were recruited to perform 2 exercise tests on cycle-ergometer. First, an 8-12-min incremental test (test 1) where oxygen uptake (VO2), heart rate (HR), blood pressure (BP), and blood lactate (La) were measured at rest and after each 2-min step. Then, at least 48-hr. after the first test, a 3-step steady state exercise test (test 2) was performed measuring VO2, HR, BP, and La. The three steps were performed at the following exercise intensities according to La: 0-2 mmol/L, 2-4 mmol/L, and 4-6 mmol/L. During both tests, blood flow patterns were determined by high-definition ultrasound and Doppler on the brachial artery. These measurements allowed to determine blood flow velocities and directions during exercise. RESULTS: On test 1 VO2, HR, BP, La, and antegrade blood flow velocity significantly increased in an intensity-dependent manner (repeated measures ANOVA, P<0.05). Retrograde blood flow velocity did not significantly change during test 1. On test 2 all the previous variables significantly increased in an intensity-dependent manner (repeated measures ANOVA, P<0.05). CONCLUSIONS: These results support the hypothesis that exercise-induced ESS might be increased in an intensity-dependent way and blood flow patterns during incremental and steady-state exercises include both antegrade and retrograde blood flows.